1998
DOI: 10.1161/01.cir.98.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-term Smoking on Myocardial Blood Flow, Coronary Vasomotion, and Vasodilator Capacity

Abstract: The normal hyperemic response to dipyridamole in long-term smokers indicates a preserved endothelium-independent coronary vascular smooth muscle relaxation, whereas the abnormal response to cold suggests a defect in coronary vasomotion likely located at the level of the coronary endothelium. Its severity depends on the total exposure time to smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
100
1
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(122 citation statements)
references
References 52 publications
(42 reference statements)
16
100
1
5
Order By: Relevance
“…Second, smokers are likely to have atherosclerotic lesions, a local and chronic inflammation of vessel walls. Smokers have a tendency to have dyslipidemia, coronary vasomotor reactivity, platelet aggregation, and a prothrombotic state [36][37][38] . Accumulation of these risk factors promotes the initiation and progression of atherosclerosis.…”
Section: Fig 2 Relationships Of Hs-crp To Fasting Iri In Nonsmokersmentioning
confidence: 99%
“…Second, smokers are likely to have atherosclerotic lesions, a local and chronic inflammation of vessel walls. Smokers have a tendency to have dyslipidemia, coronary vasomotor reactivity, platelet aggregation, and a prothrombotic state [36][37][38] . Accumulation of these risk factors promotes the initiation and progression of atherosclerosis.…”
Section: Fig 2 Relationships Of Hs-crp To Fasting Iri In Nonsmokersmentioning
confidence: 99%
“…9 -11 Moreover, smoking is associated with microvascular endothelial dysfunction that may limit the ability of epicardial revascularization to restore normal coronary blood flow. 12,13 Finally, recent studies have shown that smoking is associated with reduced exercise capacity after PTCA 14 and impaired functional capacity after bypass surgery. 15 Little is known, however, about the specific effects of smoking on overall health-related quality of life after PTCA.…”
Section: See P 1340mentioning
confidence: 99%
“…Coronary endothelial dysfunction is the earliest abnormality in the development of coronary atherosclerosis and is also independently associated with future cardiac events [2]. Several coronary risk factors adversely affect endothelial function [3][4][5][6]. Among these risk factors, smoking is the leading cause of preventable cardiovascular death and is a related factor in more than 450,000 deaths annually in the United States [7].…”
Section: Introductionmentioning
confidence: 99%